NEW MEDIA DAN REPRESENTASI BUDAYA ISLAM POPULER DI KALANGAN PENDAKWAH MUSLIM MILENIAL DI INDONESIA - Syarif, Zainuddin; Hannan, Abd; Sulaeman, Mubaidi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This study aims to conduct an in-depth analysis of the emergence of da'wah using new media (social media) in Indonesia and its role in producing a new popular Islamic culture among millennial preachers in Indonesia. Methodologically, this study used qualitative research with a netnographic approach. Two types of data sources, primary and secondary, were used, taken from the 2015-2023 period. This study found two findings after analyzing the field data. First, the phenomenon of da'wah conducted by Hanan Attaki and Felix Siauw in the new media space, especially through the Instagram platform, creates a new popular Islamic culture involving netizens in consuming religious information. Netizens tend to be exposed to the glittering flood of information that can shift their conventional religious understanding and faith. Second, at certain levels, the contemporary da'wah model shown by Hanan Attaki and Felix Siauw can represent the presence and existence of a new popular Islamic culture in Indonesia. This is because the contemporary style shown by Hanan Attaki and Felix Siauw, in many of their da'wah activities, contains elements of mass culture and the new media industry in the form of visualization and commodification of religious dimensions, values, and meanings